2010
DOI: 10.1007/s00268-010-0749-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of the Number of Central Lymph Node Metastasis in Papillary Thyroid Carcinoma: Preliminary Report

Abstract: The number of CLN metastasis correlated with the negative prognostic factors, including tumor size, extrathyroidal extension, and lateral neck lymph node metastasis. This suggests that the number of CLN has prognostic implication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 61 publications
6
51
2
Order By: Relevance
“…Recurrence-free survival rate according to pathological T stage was 96.7% in T1, 76.5% in T2, and 84.6% in T3, and it seems that pathological T staging is not enough to predict prognosis (hazard ratio 1.53, 95% CI 0.94 to 2.51, PZ0.090). This is not consistent with the previous data (1,10,11,12) and we think that patient selection bias might have led to this conclusion, as only those with tumor size O1 cm were analyzed. Patients with tumor size !1 cm showed overall excellent prognosis and it was not meaningful to analyze the impact of central neck LN metastases.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Recurrence-free survival rate according to pathological T stage was 96.7% in T1, 76.5% in T2, and 84.6% in T3, and it seems that pathological T staging is not enough to predict prognosis (hazard ratio 1.53, 95% CI 0.94 to 2.51, PZ0.090). This is not consistent with the previous data (1,10,11,12) and we think that patient selection bias might have led to this conclusion, as only those with tumor size O1 cm were analyzed. Patients with tumor size !1 cm showed overall excellent prognosis and it was not meaningful to analyze the impact of central neck LN metastases.…”
Section: Discussioncontrasting
confidence: 92%
“…These results proved the need for new staging systems to predict accurate risk of recurrence of pN1 patients. This is consistent with the previous studies which showed that increased number of central LN metastases and LN size of larger than 3 cm were associated with poorer prognosis (1,3,10,12,13,14,17). Lang et al (11) also revealed that higher metastatic central LN ratio (over 33.34%) was an independent factor for short-term outcomes estimated by postablative stimulated serum thyroglobulin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of CLNM warrants greater attention in LLN following thyroidectomy and CLN dissection. LLNM is associated with high rates of recurrence and distant metastasis and should be managed more aggressively when it is suspicious (28). Therefore, given the higher risk of LLN involvement, lateral compartment dissection might be considered a choice for these CLNM positive patients or for those with no less than 2 CLNM (29).…”
Section: Discussionmentioning
confidence: 99%
“…In some 5-10% of cases, N1b disease (lateral lymph node metastasis) may skip the central neck, usually in cases where the tumour is located in the upper poles of the thyroid (29). The most widely recognized pathological variable associated with central neck metastasis in advanced PTC is extrathyroidal invasion usually, but not always, associated with large tumours (28,30,31).…”
Section: How Often Is the Central Neck Compartment Involved In Non-mimentioning
confidence: 99%